Legal Aspects of the Rights of Children from Siri Marriages - Prasetia, Yoga; Muhamad Hasan Sebyar (Jurnal Hukum Keluarga, 2024)
Marriage is a sacred agreement to form a family between a man and a woman, even if it is carried out in a siri or registered marriage. However, there are still many ordinary people who do not understand the risks of children's rights from unregistered marriages. The rights of children from unregistered marriages are often neglected, because unregistered marriages will make the rights of children from unregistered marriages also unregistered, because children resulting from unregistered marriages will be categorized as illegitimate children or can also be said to be illegitimate children, so The position of children resulting from unregistered marriages is equated with children resulting from adultery, thus giving the legal consequence that there is no civil relationship between the biological father and children resulting from unregistered marriages. The aim of this research is to determine the legal aspects and rights of children resulting from unregistered marriages and to find out whether the rights of children resulting from unregistered marriages are the same as the rights of children resulting from legal marriages. This research uses the triangulation method. The types of data used are primary data and secondary data. The primary data used is a previous research journal written by Ari Rianti with the research title Sirri's Marriage and Its Implications for Harmony in the Household in Rejo Basuki Village, Seputih Raman District, Central Lampung Regency. previous research journal written by Maulidyah Permata Hani, et al with the title Siri Marriage in the Perspective of Islamic Law Between Religious Truth and Social Interests. Meanwhile, the secondary data is supported by a research journal written by Nur Rofiq, et al with the research title Siri Marriage and Its Influence on Child Custody Viewed from the Perspective of Religious Courts. The result of this research is that the biological father of the child carries out his obligations as stated in the Constitutional Court Decision Number 46/PUU-VIII/2010, namely fulfilling the right to earn a living, the right to inherit, and the right to receive marital guardianship if the child outside of marriage is a girl.